A Posthumanist Unsmoothing of Narrative Smoothing. (December 2020) - Cirell, Anna Montana; Sweet, Joseph David
Researchers assert that narratives do political work. Yet, in this article, we trouble the nature of this political work to account for narrative inquiry's smoothing over of polyvocality for univocal coherence. Our posthumanist unsmoothing builds an analytical example around three successive Latourian tasks to bring to the fore competing voices and truths often obscured in conventional narrative. Drawing from ethnographic data of one low-income rural family, we seek to complicate the human-centered deficit perspective. In teasing out various voices and sociotechnical systems, this posthuman analytic exposes the hidden ways in which human lives are conditioned by political forces, which order the human conscious. As ethical beings, we take responsibility for promoting analytical tools as a means of addressing advocacy as well as social justice concerns. Ultimately, we expose implications for a narrative unsmoothing that rethinks democracy and political efforts to reclaim the voice of the marginalized, such that it can dismantle deficit perspectives, inform greater sociopolitical understandings, and mobilize more just democracies. Our task as critical scholars is to carve provocative methodological spaces for new lines of inquiry that expand our horizon of hope.